NILAI PENDIDIKAN KARAKRER DALAM CERITA MASYARAKAT SINGKAWANG (KAJIAN SEMIOTIKA) - Yati, Umni; Priyadi, Antonius Totok; Seli, Sesilia (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
This research aims to determine the value of character education in the stories of the Singkawang community through semiotic studies and implementation plans in school learning. The method used in the research is a qualitative descriptive method, Charles Sanders Peirce's Semiotoka approach. The data source is a collection of stories from the Singkawang Community, analysis data in the form of quotations which have an indication of the value of character education in the form of icons, indexes and symbols in the stories of the Singkawang Community in the story of Antu Panyago Umo which represents South Singkawang District, the story of the Legend of the Dragon Statue which represents West Singkawang District , the story of the Legend of Blue Lake which represents Central Singkawang District, the story of the Legend of Batu Belimbing Wasiat Negeri Mayolaka which represents East Singkawang District, as well as the story of the Mystery of Arung Raden which represents North Singkawang District and the results of research and stories of the Singkawang Community have the opportunity to be implemented in Indonesian language learning in high school classes X/ I on KD 3.7 and KD 4.7